To study maternal hypotension, side-effects and fetal acid-base balance during cesarean delivery under spinal anesthesia using prophylactic infusion doses of 25 and 50 μg/Min phenylephrine - R Akshay; Jeetendra Kumar Bajaj (Wolters Kluwer Medknow Publications, 2023)
Objectives: To study maternal hypotension, side effects, and fetal acid-base balance during cesarean delivery under spinal anesthesia using prophylactic infusion doses of 25 and 50 μg/min phenylephrine. Methods: This prospective randomized study was carried out at a tertiary care hospital on 100 pregnant women who underwent caesarean section under subarachnoid block. The participants were randomized into: Group P1 (n = 50): who received phenylephrine 25 μg/min infusion prophylactically and Group P2 (n = 50) received phenylephrine 50 μg/min infusion prophylactically. The two groups were compared for heart rate, blood pressure, side effects, and fetal arterial and venous blood gas analysis. P value < 0.05 was considered statistically significant. Results: In group P1, 3 (6%) patients had episode of hypotension and in group P2, 1 (2%) patient had episode of hypotension. There was no incidence of hypertension in group P1 but in group P2, 5 (10%) patients had hypertension (p < 0.05). There was no episode of bradycardia or oxygen desaturation in any group. Side effects were Grade 1 in three patients each in both the groups, and Grade 2 in one patient of Group P1 and four patients in Group P2 (p = 0.842). Fetal acid-base balance was comparable in the two groups (p > 0.05). Conclusion: It can be concluded that 50 μg/min phenylephrine was able to better prevent maternal hypotension with comparable side-effects profile and fetal acid base balance.